The Uneven Geography of Access to Live Performances of Western Classical Music in the United States - Will Jones; Junghwan Kim (Findings)
This study evaluates accessibility to live performances of Western classical music across 3,109 U.S. counties. It analyzes 100 popular concertos and symphonies from this genre (e.g., Beethoven's Symphony No. 9, *Ode to Joy*) to reveal socio-spatial disparities. Midwestern counties show poorer accessibility than West and East Coasts, with the highest mean accessibility scores in the fall and the lowest in summer. A hurdle model indicates that counties with higher population density are significantly associated with greater accessibility. An interactive online StoryMap embedded with recorded performances offers a synesthetic experience for exploring accessibility to live Western classical music performances.